School-Based Health Service Programs and Early Childhood Growth and Development: Evidence from an Indonesian Kindergarten - Anggie Mursita Sari; Nailah Mumtazah; Nur Asikin (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Health services in early childhood education are crucial for supporting holistic growth and development. Integrating health programs in early learning settings facilitates early detection of developmental delays, promotes nutritional health, and strengthens family and institutional engagement. Research on the practical implementation of such programs in Indonesian early childhood education remains limited. Aims and scope of paper: This study examines the implementation of health service programs at Mutiara Idaman Kindergarten, focusing on early detection of child growth and development, collaboration with community health centers (Puskesmas) and other health institutions, and the role of parental and institutional involvement in program effectiveness. Methods: A qualitative descriptive approach was employed. Data were collected through in-depth interviews with the principal and vice principal, and through direct observations of program activities. Data analysis followed the stages of reduction, display, and conclusion drawing. Results: Two main programs were identified: the “Toddler Excursion” program in collaboration with the Puskesmas, including growth assessments, nutrition provision, and health facility orientation; and the Early Detection of Growth and Development program with Anna Medika and Muntia Husada University, focusing on developmental screening prior to kindergarten enrollment. Both programs feature intensive collaboration between educational and health institutions, active parental participation, and procedural adaptations to contextual challenges, including the COVID-19 pandemic. Main challenges include logistics coordination, sensitive communication with parents, and program continuity. Contribution: The programs demonstrate the effectiveness of integrating health services within early childhood education to support holistic child development. They enable early identification of developmental delays, promote family awareness and engagement in child health, and generate reliable data for evidence-based follow-up interventions. This study contributes to global understanding of best practices for school-based health programs and provides actionable recommendations for early learning institutions seeking to implement collaborative, health-oriented initiatives that optimize child growth and developmental outcomes.